Aqueous extract of Solanum nigrum attenuates Angiotensin-II induced cardiac hypertrophy and improves cardiac function by repressing protein kinase C-ζ to restore HSF2 deSUMOlyation and Mel-18-IGF-IIR signaling suppression. (10th February 2022) - Lin, Hung-Jen; Mahendran, Ramasamy; Huang, Hsiang-Yen; Chiu, Ping-Ling; Chang, Yung-Ming; Day, Cecilia Hsuan; Chen, Ray-Jade; Padma, V. Vijaya; Liang-Yo, Yang; Kuo, Wei-Wen; Huang, Chih-Yang
Abstract: Ethnopharmacological relevance: Solanum nigrum, commonly known as Makoi or black shade has been traditionally used in Asian countries and other regions of world to treat liver disorders, diarrhoea, inflammatory conditions, chronic skin ailments (psoriasis and ringworm), fever, hydrophobia, painful periods, eye diseases, etc. It has been observed that S . nigrum contains substances, like steroidal saponins, total alkaloid, steroid alkaloid, and glycoprotein, which show anti-tumor activity. However; there is no scientific evidence of the efficacy of S . nigrum in the treatment of cardiac hypertrophy. Aim: To investigate the ability of S. nigrum to attenuate Angiotensin II - induced cardiac hypertrophy and improve cardiac function through the suppression of protein kinase PKC-ζ and Mel-18-IGF-IIR signaling leading to the restoration of HSF2 desumolyation. Materials and methods: Cardiomyoblast cells (H9c2) were challenged with 100 nM Angiotensin-II (AngII) for 24 h and were then treated with different concentration of S . nigrum or Calphostin C for 24 h. The hypertrophic effect in cardiomyoblast cells were determined by immunofluorescence staining and the modulations in hypertrophic protein marker along with Protein Kinase C-ζ, MEL18, HSF2, and Insulin like growth factor II (IGFIIR), markers were analyzed by western blotting. In vivo experiments were performed using 12 week old male Wistar Kyoto rats (WKY) and Spontaneously hypertensive rats (SHR) separated into five groups. [1]Control WKY, [2] WKY –100 mg/kg of S . nigrum treatment, [3] SHR, [4] SHR-100 mg/kg of S . nigrum treatment, [5] SHR-300 mg/kg of S . nigrum treatment . S. nigrum was administered intraperitoneally for 8 week time interval. Results: Western blotting results indicate that S . nigrum significantly attenuates AngII induced cardiac hypertrophy. Furthermore, actin staining confirmed the ability of S . nigrum to ameliorate AngII induced cardiac hypertrophy. Moreover, S . nigrum administration suppressed the hypertrophic signaling mediators like Protein Kinase C-ζ, Mel-18, and IGFIIR in a dose-dependent manner and HSF2 activation (restore deSUMOlyation) that leads to downregulation of IGF-IIR expression. Additionally in vivo experiments demonstrate the reduced heart sizes of S. nigrum treated SHRs rats when compared to control WKY rats. Conclusion: Collectively, the data reveals the cardioprotective effect of S. nigrum inhibiting PKC-ζ with alleviated IGF IIR level in the heart that profoundly remits cardiac hypertrophy for hypertension-induced heart failure. Graphical abstract: Graphical diagram mention that ang II induced PKC signaling pathway through AT1 R receptor, further activated MEL-18 to suppress the HSF2 Sumolyation, Finally IGF-IIR up-regulated to induced Cardiac hypertrophy. The study aimed to treat with Solanum nigrum to obstruct AT1 R receptor further attenuate PKC and MEL-18 expression for HSF2 activation (deSumoylation) that leads to down regulate the expression of IGF-IIR. Image 1 Highlights: PKC signaling pathways regulated insulin-like growth factor II receptor (IGF-IIR) expression via mTORC1 signaling in ANG II-induced cardiac hypertrophy. Furthermore, treatment with S. nigrum ameliorated hypertension, particularly diastolic pressure, and markedly restored deSUMOylation of HSF2 to inhibit upregulation of IGF-IIR expression. PKC-ζ expression in turn down regulated IGF-IIR expression and decreased hypertension-induced cardiac hypertrophy.